Relationship between serum thyroid hormones and their associated metabolites, and gene expression bioindicators in the back skin of Rana [Lithobates] catesbeiana tadpoles and frogs during metamorphosis - Poulsen, Rikke; Jackman, Shireen H.; Hansen, Martin; Helbing, Caren C. (Frontiers in Endocrinology, 2023)
Anuran metamorphosis is characterized by profound morphological changes including remodeling of tissues and organs. This transition is initiated by thyroid hormones (THs). However, the current knowledge of baseline levels of THs during metamorphosis relies on pooled samples using methods known for high variability with little reporting of measured variation. Moreover, establishing a clear linkage between key gene expression bioindicators and TH levels throughout the metamorphic process is needed. Using state-of-the-art ultra-high performance liquid chromatography isotope-dilution tandem mass spectrometry, we target 12 THs -and metabolites in the serum of Rana [Lithobates] catesbeiana (n=5-10) across seven distinct postembryonic stages beginning with premetamorphic tadpoles (Gosner stage 31-33) and continuing through metamorphosis to a juvenile frog (Gosner stage 46). TH levels are then related to TH-relevant gene transcripts (thra, thrb, and thibz) in back skin of the same individual animals. Significant increases from basal levels were observed for thyroxine (T4) and 3,3’,5-triiodothyronine (T3) at Gosner stage 41, reaching maximal levels at Gosner stage 44 (28±10 and 2.3±0.5 ng/mL, respectively), and decreasing to basal levels in juvenile frogs. In contrast, 3,5-diiodothyronine (T2) increased significantly at Gosner stage 40 and was maintained elevated until stage 44. While thra transcript levels remained constant and then decreased at the end of metamorphic climax, thrb and thibz were induced to maximal levels at Gosner stage 41, followed by a decrease to basal levels in the froglet. This exemplifies the exquisite timing of events during metamorphosis as classic early response genes are transcribed in anticipation of peak TH concentrations. Interestingly T2 showed a distinct concentration profile suggesting a specific biological role of this biomolecule in anuran postembryonic development. This finding also underlines the sensitivity of the developmental process, and it is, indeed, well-known that external factors such as anthropogenic chemicals can disrupt anuran metamorphosis. Hence, as a second aim of the study, we set out to find additional bioindicators of metamorphosis, which can aid future investigations of developmental disruption. Using a sensitive nanoLC-Orbitrap system an untargeted analysis workflow was applied. Among 6,062 endogenous metabolites, 421 showed metamorphosis-dependent concentration dynamics. These potential bioindicators included several carnitines, prostaglandins and some steroid hormones.